Navinsilk Tailoring Management System - Rajagobal, Nanthini; Noraini Ibrahim (Applied Information Technology And Computer Science, 2025)
NavinSilk Tailoring Shop, a custom tailoring service, has built a reputation for quality craftsmanship but now faces significant operational challenges due to its reliance on manual processes. To address issues such as long customer wait times, inaccurate order tracking, and inefficiencies in workflow management, a web-based management system was developed using the Prototyping Model. This iterative approach enabled continuous user feedback and refinement. The system comprises seven modules: login and sign-up, manage profile, manage stitching type, manage workers, generate report, manage order, and manage appointment and view order status. Developed using an object-oriented approach, the web application leverages PHP, JavaScript, HTML, and CSS to streamline operations. The testing results show that 100% of the features function properly as expected. In conclusion, the NavinSilk Tailoring Management System has successfully digitized order management, customer interactions, and workflow tracking, significantly enhancing operational efficiency, accuracy and customer satisfaction while establishing a new benchmark for excellence in the tailoring industry.